Ligasure-Assisted Laparoscopic Sutureless Appendectomy: A Prospective Clinical Evaluation Of Effectiveness And Benefits - Kumar, Vivek; Khandelwal, Shivam; singh, Prakhar; Husain, Mohd Zafar (Journal of Neonatal Surgery, 2025)
Background. Laparoscopic appendectomy has progressively replaced the open technique owing to decreased postoperative pain, earlier mobilisation, and shorter hospital stay. Ensuring secure closure of the appendiceal stump, however, remains pivotal to avert intra‑abdominal sepsis. LigaSure™ tissue‑fusion technology merges pressure with bipolar energy to provide a rapid, haemostatic seal of vessels and tissue bundles ≤ 7 mm. We prospectively evaluated the safety and efficacy of the 5‑mm LigaSure™ vessel‑sealing system for entirely suture‑less laparoscopic appendectomy. Methods. Between July 2022 and July 2023, 57 consecutive patients with uncomplicated acute appendicitis underwent laparoscopic appendectomy at a tertiary‑care centre using LigaSure™ alone to divide the meso‑appendix and seal the appendiceal base. Demographics, operative duration, return of bowel function, length of stay (LOS), and peri‑operative complications were recorded. Data were analysed with descriptive statistics. Results. The cohort comprised 32 males and 25 females (mean age 28.4 ± 9.6 years; range 15–65). Mean operative time was 34 ± 5.7 min; no conversion to open surgery occurred. Bowel sounds returned on postoperative day (POD) 1 in 84.2 % of patients, and oral feeds were resumed at 2.1 ± 0.5 days. Mean LOS was 3.6 ± 0.7 days. Minor morbidity was noted in three patients (5.2 %): low‑grade fever (n = 1) and superficial port‑site infection (n = 2). There were no intra‑abdominal abscesses, stump leaks, re‑operations, or mortality. Conclusion. LigaSure™ permits a swift, single‑device, suture‑less laparoscopic appendectomy with negligible morbidity and without increasing cost in publicly funded settings. The technique obviates endo‑loops or staplers, minimises instrument exchange, and may shorten operative time. Larger randomised trials are warranted to confirm these favourable early outcomes.